Effect of semi-active control utilizing damper joint stiffness on the dynamic performance of 25T passenger cars - HOU Yuxuan; HUANG Zhihui; CHEN Xuejing; TIAN Mingjie; JIANG Hui; YAN Bohan (机车电传动, 2025)
This study aims to enhance the lateral stability performance of 25T passenger cars during operation. To this end, a secondary transverse damper model was constructed using Matlab/Simulink, based on an on-off skyhook damping semi-active control strategy. Dynamics simulation analysis was carried out in conjunction with Simpack, which specializes in multi-body dynamics. The analysis considered the influence of damper joint stiffness on the semi-active control effect, building on the traditional semi-active control model. A comparative analysis was performed to investigate the effects of passive control, traditional semi-active control, and semi-active control utilizing damper joint stiffness on the running smoothness, running stability and curve negotiation performance of the vehicles. The effect of time lag on the control effect was also examined. The simulation results indicate that the semi-active control significantly improves the lateral stability performance of the vehicles, but it reduces their nonlinear critical speed. Compared to passive control, traditional semi-active control and semi-active control utilizing joint stiffness resulted in a decrease in the lateral Sperling index by 14.5% and 15.8%, respectively, and a reduction in the nonlinear critical speed by 8.09% and 6.93%, respectively. Additionally, no significant effects were identified on the curve negotiation performance with these two control modes, indicating adequate safety margins. Study results also suggest that controlling the response time-lag of the system within 80 ms is essential to ensure the effect of semi-active control.